The Effect of Increasing Carbon Concentration Increasing on the Mechanical Properties of TiCx Thin Films - Al-Ghaban, Ahmed M. H. Abdulkadhim (Al-Khwarizmi Engineering Journal, 2017)
Carbides or nitrides thin films present materials with good mechanical properties for industrial applications as they can be coatings at low temperatures serve temperature sensitive surfaces. In this work the effect of the C percentage on the mechanical properties represented by the Young modulus (E) of combinatorial magnetron sputtered TiCx (34%x˂65%) has been studied. The structure of the produced films is TiC independent on the C concentration. The mechanical properties are increased with increasing the C concentration up to 50%, and then decreasing with further C % increasing. These results can be explained by considering the resultant residual stresses.